PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN PRODUK UMKM DI MASA PANDEMI COVID-19 DESA SEMBAYAT - Wardana, Dodi Jaya; Aini, Assuratul (Jurnal Pengabdian Masyarakat dan Lingkungan, 2022)
The purpose of this program is to provide knowledge to MSME actors in Sembayat Village, Manyar District, Gresik Regency about how to promote a MSME product or service on a Social Media Platform that is simple and easy to understand by the Sembayat Village community. The method used is BIMTEK (Technology Guidance), assistance and strengthening in the production process through this method the production process will be effective and efficient, so as to produce quality products. Business development can be done by expanding marketing. Facebook and Instagram are one of the media that can be used to do marketing in the home industry. Through one of the platforms above, home industry owners can develop their business with a wider market, so that businesses can still thrive in the midst of a pandemic.